ICRF mode conversion efficiency in a two-ion component plasma of a tokamak - Grekov, D.L.; Kasilov, S.V.; Tretjak, K.K. (Вопросы атомной науки и техники, 2011)
Mode conversion of fast magnetosonic wave (FMSW) into a short-wavelength wave is studied in the presence of ion cyclotron absorption and direct electron damping in a tokamak plasma. In plasmas with two (a majority and a light minority) ion species, FMSW launched from the low-field side ICRF antenna can convert to a slow mode which runs towards the minority cyclotron resonance point, if the component of confining filed along the big radius of torus is sufficiently large. The efficiency of conversion has been studied with the help of one-dimensional code which computes full-wave solution of Maxwell equations with cold plasma conductivity. The dependencies of conversion efficiency on plasma density and minority concentration have been established.